Deciphering Sukuk Rating Methodology During Financial Crisis in Malaysian Capital Market Industry - Mahfudz, Akhmad Affandi; Sofyan, Hidayat; Hadiyati, Puji (International Journal of Engineering and Technology, 2018)
As Sukuk regarded as certificate of investment, rating becomes a vital measurement to mobilize resources. Malaysia recorded to be the largest Sukuk market in the world. This paper aims to examine the determinant of Sukuk rating methodology that applied in Malaysia and also examines its level of significance. This paper employs ordinal logistic regression model by utilizing financial and non financial ratios such as company growth, firm size, profitability, liquidity, leverage ratio, and Sukuk and bond maturity. This study found that leverage ratio to be significant as Sukuk determinant rating for Malaysia. Meanwhile, the significance level among Sukuk determinant for this country are: growth accounted for 0.118. Firm size 0.067, Profitability account for 0.934 respectively. Liquidity with 0.163 and Leverage ratio 0.037. The study concludes that during financial crisis Malaysia showed robustness and found to be resilient. This implies that Malaysia need to do promptly on risk mitigation particularly market risk as well as internal political stability of the country as investors and issuers of sukuk taking into account the performance of these risks.